"Delivering an information resources service to users’ homes to ensure Healthcare during COVID -19: Case study" - Muntaha Abdul Kareem Jasim (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
University college libraries are one of the most important information institutions for all researchers during their research and study life, they seeks to provide information sources such as; books, periodicals, theses, databases, Inquiry service and answering questions services in various disciplines to achieve its goals. In 2020, college libraries of all types stepped up to meet the needs of their users’ as they responded to the impacts of COVID-19, also extended necessary lifelines to community members facing job losses, healthcare crises, and remote work and learning during an unprecedented and uncertain time. The research aim to identifying the services provided to the postgraduate students users at University of Baghdad college libraries at Al-Jadriya campus, and to in light of the provision of remote services 1/2/2020-30/5/2021 Research methodology used a questionnaire tool distributed for random sample about (55) male and female students was selected, consisting of (25) doctoral students and (30) master’s students. With different specializations (scientific and humanitarian), and the research suggested and recommended: 1. Allow to the users to visit the college libraries while maintaining social distancing between them and information providers. 2. Providing home delivery service, by training workers to be information delivery services, and providing them all supplements for the purpose of ensuring the success of this service. 3.Adopting a set of applications available to facilitate the access of resources to the users in their homes without the need to visit libraries, such as (Curbside Communicator), The Princh application, etc.